P162 Effect of adding propranolol or increased inhaled corticosteroid dose in persistent asthma. (14th November 2013) - Anderson, WJ; Short, PM; Williamson, PA; Manoharan, A; Lipworth, BJ
Abstract : Introduction and Objectives: Chronic propranolol does not improve airway hyper-responsiveness (AHR) in persistent asthmatics taking medium dose inhaled corticosteroid (ICS), 440µg/day 1 . We wished to assess for any putative corticosteroid-sparing effect of propranolol added to low dose ICS versus higher dose ICS, on histamine AHR. Methods: We conducted a randomised double-blind placebo-controlled crossover trial in mild-moderate persistent asthmatics. Patients were run-in for 2 weeks on hydrofluoroalkane-beclometasone dipropionate (HFA-BDP) 100µg/day. Patients were then randomised to either: propranolol 80mg/day plus HFA-BDP 100µg/day; or placebo plus HFA-BDP 400µg/day, each for 4 weeks. Propranolol was up-titrated to 80mg/day for the second 2 weeks of treatment. Patients received tiotropium 18µg/day during run-in and both treatments, which was subsequently discontinued 5 days prior to histamine challenge (primary outcome). Results: 16 patients completed, mean: age 38yr; FEV1 86.4%; Histamine PC20 1.39mg/ml; ICS 406µg/day. Histamine PC20 remained unchanged adding propranolol to HFA-BDP100 compared to baseline (HFA-BDP100): 0.17 doubling dilution (dd) difference (95%CI -0.58–0.92), but there was a significant improvement with HFA-BDP400 compared to both baseline 1.05dd (95%CI 0.43–1.66), P = 0.02; and propranolol 0.88dd (95%CI 0.45–1.30), P = 0.006 (Figure 1a ). Significant improvements from baseline were observed with HFA-BDP400 for exhaled nitric oxide, blood eosinophils (Figure 1b ) and Asthma Quality of Life Questionnaire (AQLQ) symptom score (Figure 1c ), but not with propranolol. Salbutamol recovery time post-challenge was partially blunted by propranolol (median prolongation 5min compared to both baseline and HFA-BDP400, P = 0.002). Domiciliary evening FEV1 also fell with propranolol (mean reduction from baseline 0.22L [95%CI 0.10–0.34L], P = 0.012) while Asthma Control Questionnaire (ACQ) showed no significant changes with either treatment compared to baseline. Conclusions: In mild-moderate persistent asthmatics, propranolol produced no additive effects on top of low dose ICS, while further significant improvements in AHR and inflammation were seen with a higher dose of ICS. Propranolol attenuated salbutamol recovery and reduced evening FEV1, but not ACQ or AQLQ. References: Short PM, Williamson PA, Anderson WJ, Lipworth BJ. Randomised placebo- controlled trial to evaluate chronic dosing effects of propranolol in asthma. Am J Respir Crit Care Med 2013;187:1308–1314.